Aspects of Roman History 82BCAD14 : a Source-based Approach. - Davies, Mark Everson (Aspects of Classical Civilization., 2010)
Examines the political and military history of Rome and its empire in the Ciceronian and Augustan ages. This book covers the lives of women and slaves, the running of the empire and the lives of provincials, and religion, culture and propaganda in the period of 82BC-AD14. It is suitable for the students of Roman history.